Safety and efficacy of a feed additive consisting of a preparation of carvacrol, thymol, d‐carvone, methyl salicylate and l‐menthol (Biomin® DC‐P) for all poultry species (Biomin GmbH). (7th September 2022) - ; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Durjava, Mojca Fašmon; Kouba, Maryline; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on the safety and efficacy of a preparation of carvacrol, thymol, d ‐carvone, methyl salicylate and l ‐menthol (Biomin ® DC‐P) for all poultry species. The additive is authorised for use in feed for chickens for fattening, chickens reared for laying and minor poultry species reared to the point of lay. The safety and efficacy of the additive for those species have been previously evaluated by the EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP Panel). The current application is for an extension of use of the additive for all poultry species under the same conditions of use (recommended level ranging between 65 and 105 mg/kg complete feed). The FEEDAP Panel concluded that the additive Biomin ® DC‐P is safe for poultry species for fattening or reared for laying, but in the absence of adequate data cannot conclude on the safety for laying/breeding birds. The use of Biomin ® DC‐P in feed for all poultry species under the proposed conditions of use was considered safe for consumers and the environment. The FEEDAP Panel considered that exposure of users by inhalation is unlikely. In the absence of data, the Panel could not conclude on the effects of Biomin ® DC‐P on skin and eyes. Biomin ® DC‐P has the potential to be efficacious in poultry species for fattening or reared for laying when incorporated into feed at a minimum concentration of 65 mg/kg complete feed. In the absence of sufficient data, the Panel could not conclude on the efficacy for laying hens or for other poultry species for laying/breeding.